Social Movement Learning for a Just Transition in Appalachia - COLLEEN UNROE (Adult Education Research Conference, 2019)
This article explores Just Transition and social movement learning as a part of community development and organizing strategies to move beyond coal in Appalachia.
Keywords: just transition; social movement learning; Appalachia; popular education